2007
DOI: 10.4049/jimmunol.179.9.5728
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of the Nature and Functions of Dendritic Cells and Macrophages by Cathepsin E

Abstract: The aspartic proteinase cathepsin E is localized mainly in the endosomal structures of APCs and has been implicated in a variety of immune responses, however, the precise roles of cathepsin E in these cells remain speculative. In this study, we report the effect of disrupting the gene encoding cathepsin E on the nature and functions of dendritic cells (DCs) and macrophages derived from mouse bone marrow precursors, as well as mouse peritoneal macrophages. Whereas cathepsin E deficiency induced the accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 56 publications
(57 reference statements)
3
38
2
Order By: Relevance
“…However, contrasting results were seen when macrophages and DC were compared, as cathepsin E null DC showed an enhanced presentation of ovalbumin, a result attributed to increased phagocytosis and elevated expression of co-stimulatory molecules [31]. Cathepsin E-deficient mice are susceptible to developing atopic dermatitis, attributed to the accumulation of both Th2 polarising cytokines and IgE.…”
Section: Antigen Processing and Presentationmentioning
confidence: 97%
See 2 more Smart Citations
“…However, contrasting results were seen when macrophages and DC were compared, as cathepsin E null DC showed an enhanced presentation of ovalbumin, a result attributed to increased phagocytosis and elevated expression of co-stimulatory molecules [31]. Cathepsin E-deficient mice are susceptible to developing atopic dermatitis, attributed to the accumulation of both Th2 polarising cytokines and IgE.…”
Section: Antigen Processing and Presentationmentioning
confidence: 97%
“…Loss or inhibition of cathepsin E has been reported to compromise processing and presentation of antigens such as ovalbumin, myoglobin and tetanus toxin [31,32]. However, contrasting results were seen when macrophages and DC were compared, as cathepsin E null DC showed an enhanced presentation of ovalbumin, a result attributed to increased phagocytosis and elevated expression of co-stimulatory molecules [31].…”
Section: Antigen Processing and Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cathepsin E is predominantly found in immune-related cells, including macrophages, dendritic cells, and microglia [3,4] or in the epithelial cells of the gastrointestinal mucosa and skin [5,6]. To investigate the physiological or pathological roles of the proteinase in vivo, we have previously generated cathepsin E-deficient (CatE -/-) mice.…”
Section: Introductionmentioning
confidence: 99%
“…The chemotactic receptors belong to the 7-transmembrane-G-protein-coupled receptor family, and trigger various immune responses besides chemotaxis, induce the production of reactive oxygen species, and stimulate the release of proteolytic enzymes from granules, in the case of neutrophils (17). Concerning chemotactic responses, we have more recently reported that bone-marrow derived macrophages from CatE -/-mice display impaired chemotaxis in responses to a chemokine and a bacterial peptide (18).…”
Section: Introductionmentioning
confidence: 99%